The impact of canine-assisted intervention on stress reduction among university students in Thailand - Saengduean Yotanyamaneewong; Daranee Junla; Janine L. Brown; Nathida Siriapaipant; Naruedee Yodkamol; Worapat Prachasilchai; Adul Saengthong; Pratch Sanguansak; Thanapun Kankonsue; Veerasak Punyapornwithaya; Chalutwan Sansamur; Korakot Nganvongpanit; et al. (PLoS ONE, 2025)
Stress negatively impacts university students, leading to adverse outcomes. While canine-assisted intervention (CAI) has been shown to reduce self-reported stress, no studies have investigated stress levels and associated biomarkers in dogs and students simultaneously. This study examined salivary cortisol, blood pressure, and pulse rate in 122 university students experiencing self-reported moderate to high stress before an encounter with a dog (T1), immediately before meeting a dog (T2), and after spending 15 minutes interacting with a dog (T3). Participants assessed their stress level using a visual analog scale, and blood pressure and pulse rate were measured at three time points. Salivary cortisol was also measured at T1 and T3. Six privately owned dogs, all in good health and comfortable with strangers, participated in the intervention sessions. Salivary and fecal cortisol samples from the dogs were collected in the morning before commencing activities, at noon, and in the evening after human interactions ended. The results showed that the expectation of interacting with dogs reduces self-reported stress, pulse rate, and salivary cortisol, which remained significantly lower after the interaction. Salivary cortisol concentrations in dogs did not differ throughout the day. By contrast, fecal glucocorticoid metabolite concentrations during the week dogs interacted with students were higher (P =  0.0012) than those during the week post-experiment, which, based on behavior, appeared to indicate positive stimulation. These findings highlight the potential of integrating CAI into university stress management programs. Future research could explore extending these benefits to community dogs, long-term effects, and enhancing accessibility to this form of stress relief.